2016
DOI: 10.1007/s10549-016-3738-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ALDH1 on prognosis and chemoresistance by breast cancer subtype

Abstract: Aldehyde dehydrogenase 1 (ALDH1) has been identified as a breast cancer stem cell marker, but its value as a predictor of prognosis and chemoresistance is controversial. This study investigated the effect of ALDH1 on prognosis and chemoresponse by breast cancer subtype. We immunohistochemically analyzed 653 invasive breast cancer specimens and evaluated correlations among clinicopathological factors, survival status, response to neoadjuvant chemotherapy, and ALDH1 expression. Of 653 specimens, 139 (21.3 %) exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 35 publications
6
56
3
1
Order By: Relevance
“…Here we did not find any association between ALDH1A1 expression and clinicopathologic features in TNBC. Although ALDH1 had a significant impact on prognosis in the other subtypes, it did not appear to correlate with the survival of TNBC patients 37-39. Here we showed a borderline significant trend of ALDH1A1+ phenotype for PFS.…”
Section: Discussioncontrasting
confidence: 62%
“…Here we did not find any association between ALDH1A1 expression and clinicopathologic features in TNBC. Although ALDH1 had a significant impact on prognosis in the other subtypes, it did not appear to correlate with the survival of TNBC patients 37-39. Here we showed a borderline significant trend of ALDH1A1+ phenotype for PFS.…”
Section: Discussioncontrasting
confidence: 62%
“…The ALDH1 enzyme is another stem cell marker which is particularly useful is studies of CSCs in culture, when contamination by other stem cells (such as hematopoietic stem cells) is not relevant [52, 53]. However, it was recently proposed that there are two distinct CSC sub-populations in breast cancer, one identified as CD44+/CD24 low/− and the other as ALDH1+ [54].…”
Section: Resultsmentioning
confidence: 99%
“…[12,27] CSC markers were reported to be present in CSCs as well as in normal stem cells, [9] with ALDH1 shown to be a marker of BCSCs. As BC is one of the most common tumors in women worldwide, so we conduct this study to explore the role of ALDH1 expression in BC.…”
Section: Discussionmentioning
confidence: 99%
“…[48] Many studies showed that ALDH1 is a marker of BCSCs, [3,5,9,10] while Kunju et al [11] reported that ALDH1-positive benign breast epithelial cells may predict an increased risk for the development of BC. Several studies suggested that ALDH1 is associated with an aggressive phenotype and poor prognosis, [1216] although others found that it was not a survival predictor of BC [1719] ; another study reported that expression of the major ALDH1 isoenzyme ALDH1A1 predicted a better outcome in BC of the triple-negative subtype. [20] The prognostic value of ALDH1 in BC is therefore controversial, and has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%